Digital Transformation of Global e-Commerce Leader Amazon during the Coronavirus Pandemic - Wang Rui; Vladimir Grigoriev (Communications of International Proceedings, 2021)
COVID-19 has caught the global economy by surprise. The pandemic has hit all areas. And it changed the trends and habits of most people, which also affected a sharp turn in demand and supply for goods and services. And at this moment it turned out that those companies that actively invested in IT and innovations feel the best. IT services have become not only full-fledged, but also key in life and business during quarantine. One of these companies is the American corporation Amazon, the world leader in the e-commerce market. According to the company's financial indicators, in 2020, Amazon's net profit grew by 84% and reached a record amount of $ 21 billion. At the same time, the corporation has shown amazing growth rates in the last 3 years - on average, its revenue has increased by 30% annually. Earnings per share have also grown significantly over the past year - from $ 5.01 to $ 15.79 [8]. Truly, Amazon has a problem: the huge growth in demand is too high for the current marketplace infrastructure.
Keywords: Digitalization; Business Transformation; Pandemic; Marketplace; International Market; Competition; Innovation; Strategies; Brand.